Good governance of third party funding - Catherine Kessedjian (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2014)
Third party funding of international litigation and arbitration is controversial. As a phenomenon that presents issues distinct from other forms of litigation funding, some principles for good governance need to be developed.
Keywords: 330